Doxorubicin and cisplatin induce apoptosis in ovarian stromal cells obtained from cryopreserved human ovarian tissue. (July 2016) - Fabbri, Raffaella; Macciocca, Maria; Vicenti, Rossella; Paradisi, Roberto; Klinger, Francesca Gioia; Pasquinelli, Gianandrea; Spisni, Enzo; Seracchioli, Renato; Papi, Alessio
Aim: To investigate mechanisms by which doxorubicin (DOX) and cisplatin (CIS) cause human ovarian stroma injury.Patients & methods: Stromal cells from human cryopreserved ovarian tissue were cultured in the presence of 1 µM DOX and 10 µM CIS. Ovarian damage induced by treatments was evaluated by 'Live/Dead' and sulforhodamine-B assays, the expression of different apoptosis markers.Results: Stromal cell growth was inhibited by DOX and CIS, and this effect was accompanied by apoptosis through mitochondrial pathway activation: Bax, cleaved-caspase 9, cleaved-PARP1 induction and Akt1, Bcl2, phospho-44/42-MAPK/ERK1/2 reduction were observed.Conclusion: DOX and CIS induced apoptosis in human ovarian stromal cells. Knowledge of mechanisms by which the drugs act is important to identify possible ways to counteract side effects of chemotherapy on ovaries.